The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41467-023-37298-y
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium shift, poisoning prevention, and selectivity enhancement in catalysis via dehydration of polymeric membranes

Abstract: Generation of water as a byproduct in chemical reactions is often detrimental because it lowers the yield of the target product. Although several water removal methods, using absorbents, inorganic membranes, and additional dehydration reactions, have been proposed, there is an increasing demand for a stable and simple system that can selectively remove water over a wide range of reaction temperatures. Herein we report a thermally rearranged polybenzoxazole hollow fiber membrane with good water permselectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…More specifically, water is one of the primary byproducts of the FT synthesis reaction and its accumulation can significantly reduce the driving force of the reaction, easily resulting in catalyst deactivation [120]. To address these issues, Hyeon et al removed the water in situ by using a thermally rearranged polybenzoxazole membrane (See Figure 3), and found that the selectivity of the targeted low-carbon olefins was improved by 2~6% [121]. The aforementioned membrane reactors are still in their research and development stage and have a long way to go before their large-scale deployment.…”
Section: Co 2 Hydrogenation To Liquid Fuels Technologiesmentioning
confidence: 99%
“…More specifically, water is one of the primary byproducts of the FT synthesis reaction and its accumulation can significantly reduce the driving force of the reaction, easily resulting in catalyst deactivation [120]. To address these issues, Hyeon et al removed the water in situ by using a thermally rearranged polybenzoxazole membrane (See Figure 3), and found that the selectivity of the targeted low-carbon olefins was improved by 2~6% [121]. The aforementioned membrane reactors are still in their research and development stage and have a long way to go before their large-scale deployment.…”
Section: Co 2 Hydrogenation To Liquid Fuels Technologiesmentioning
confidence: 99%